Donald Sanders interviewed by Peter Donovan in the Australian finance sector oral history project - Sanders, Don.; Donovan, P. F. (Peter Francis), 1945- (2010)
Donald Sanders talks about his family background; his brother and childhood; the mining community and the WWII period at Keiraville; family religion; his school experiences; joining the Commonwealth Bank; gender roles in the Bank in 1940s; his commitment to a banking career and university; university life immediately post-war from 1946; mixing university and work life; his wife’s background; his career progress in the Commonwealth Bank; relationship of Commonwealth Bank to other banks; his transfer to Treasury and role; relationship between Treasury and central bank operations of the Commonwealth Bank; his return to the Economics Department; Dr H.C. 'Nugget' Coombs; bank nationalisation; banking relations with Asia; the London School of Economics; secondment to the Bank of England; return to Australia to the Reserve Bank as an economist; his career progression in the Reserve Bank; lecturing at the Asian Institute for Economic Planning and Development, Chulalongkorn University; secondment to Washington for three months.
Sanders discusses his appointment as Deputy Governor of the Reserve Bank; Whitlam Government; the Loans Affair; the Campbell Committee; award of Companion of Order of the Bath; financial deregulation; floating the Australian Dollar; entry of foreign banks to Australia; deregulation and non-banking financial institutions; his resignation as Deputy Governor; joining the Commonwealth Bank as chief executive; superannuation implications; Commonwealth Bank culture; progress of deregulation; impending competition with privatisation; the share market crash (1987) and availability of finance; new initiatives and acquisitions; exploring overseas acquisitions; acquisition of the State Bank of Victoria; privatisation of the Commonwealth Bank; marketing campaigns; his retirement and succession at the Commonwealth Bank; the Australian Chamber Orchestra; his retirement and company directorships; the receipt of the AO on Australia Day 1994; the careers of his five children; his interests outside banking; technological change; the branch network; the status of bank managers; roles of advisers and mentors; relations with federal Treasurers and others.
Recorded on 15-16 March 2010 at the National Library of Australia, Canberra, A.C.T.
Digital master available
National Library of Australia, Pictures collection PIC Online access #NL40210
Timed summary (9 p.) and uncorrected transcript (typescript, 143 leaves)
Keywords: Sanders, Don -- Interviews; Reserve Bank of Australia; Commonwealth Bank (Australia); Bankers -- Australia -- Interviews; Banks and banking, Australian -- Government policy; Banks and banking, Foreign -- Deregulation -- Australia; Bankers